2021
DOI: 10.3846/tede.2021.14508
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mobile Phones and Internet Use on Financial Inclusion: Empirical Evidence From the Eu Post-Communist Countries

Abstract: Poverty alleviation has become one of the biggest challenges for many countries and access to financial services is considered to be a key driver of development and economic growth. Finding solutions that can break down barriers that poor people are facing to access formal financial services has become a major concern for researchers, governments, financial institutions. Financial services must reinvent themselves and the adoption of new technology is a crucial key to overhaul their operations and to find inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…Furthermore, based on the study carried out by Barbesino et al (2005), the internet in Europe has emerged as a widely recognized distribution channel for the finance industry that includes traditional and new players. However, research using cross-sectional data from eleven post-communist Europe countries has identified both the positive and negative relationship between the mobile phone and internet consumption towards financial institution and market access (Bayar et al, 2021).…”
Section: Digital-focused Determinants: Influencer Of Dfimentioning
confidence: 99%
“…Furthermore, based on the study carried out by Barbesino et al (2005), the internet in Europe has emerged as a widely recognized distribution channel for the finance industry that includes traditional and new players. However, research using cross-sectional data from eleven post-communist Europe countries has identified both the positive and negative relationship between the mobile phone and internet consumption towards financial institution and market access (Bayar et al, 2021).…”
Section: Digital-focused Determinants: Influencer Of Dfimentioning
confidence: 99%
“…The integration of both interactive and traditional media tends to be more effective for marketing communication campaigns [72]. The Internet and mobile devices "have become useful tools" [73] in the digital era and this recent pandemic period. The cyber environment is a challenge and also an opportunity for both companies and consumers, where this requires persuasive information to be trustworthy [74].…”
Section: Traditional and Modern Approaches To Persuasive Marketing Co...mentioning
confidence: 99%
“…Furthermore, Khera et al (2021) note that some of the key drivers for improving financial development are represented by the quality of financial institutions as well as the levels of financial and digital education. Finally, Bayar et al (2021) analyze the linkages between digitalization and financial inclusion in EU post-communist countries and conclude that mobile cellular subscriptions can positively influence economic and financial development.…”
Section: Digitalization and Financial Developmentmentioning
confidence: 99%
“…The variables were chosen based on existing literature on financial development in relation to digitization and education, as mentioned in the Introduction, as well as economic rationale. Extant literature has used many proxies for financial development for a long time without agreeing on the ideal choice, usually considering banking system attributes and capital market characteristics, depending on the research scope and objectives (see, in this respect, King and Levine 1993;Kim and Lin 2011;Sehrawat and Giri 2015;Bist 2018;Bayar et al 2021;Cheng et al 2021;Mignamissi 2021, among many others). The acknowledgment by the International Monetary Fund (IMF) of the need to incorporate in the assessment of financial development the diversity of financial systems across countries, first evidenced by Čihák et al (2012) and further by Sahay et al (Sahay et al) led to a comprehensive set of financial development measures in the form of indexes using the methodology proposed by Svirydzenka (2016).…”
Section: Data and Data Sourcesmentioning
confidence: 99%